How Shall I Live? Constructing a Life Story in the College Years. Issue 166 (June 2014) - McAdams, Dan P.; Guo, Jennifer
Abstract : This chapter applies the concept of narrative identity to college student development. The authors describe a narrative interview method that can be used to promote the development of a purposeful life story in the college years.